Maternal and fetal outcomes in patients with systemic lupus erythematosus - Ahmed, Abdelnasir; Ibkhatra, Salem; Elbraky, Fathi; Alsaeiti, Khaled (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Objectives: Lupus is associated with a considerable risk of fetal and maternal complications. The aim of this study was to assess the maternal and fetal outcomes in pregnant women with systemic lupus erythematosus (SLE) and likely predictors of adverse outcome in Benghazi, Libya. Patients and Methods: This was a retrospective review of the outcome of sixty pregnancies among 48 SLE patients attending the rheumatology clinics at Benghazi medical center, who were pregnant from January 2008 to December 2018. Each pregnancy was counted as a separate case. Results: The mean age to conceive was 30.6±6.1 years (19–42 years). Nineteen (31.7%) patients were primigravida, and the patients' age at SLE diagnosis was 25.2 ± 5.6 years. Forty-eight of the pregnancies (80%) were planned, ten patients have preexisting hypertension (HTN), most cases were in clinical remission before pregnancy (53 patients; 88%), only seven patients were identified as having active disease, four of them had lupus nephritis based on clinical features. Secondary antiphospholipid syndrome was diagnosed in four patients. Most pregnancies (50; 83%) resulted in live birth babies, 3 (5%) of them were preterm due to preeclampsia, six pregnancies (10%) ended in spontaneous abortion, and there were four intrauterine fetal deaths. More positive cases for aCl antibodies were affected than negative cases (P = 0.005). Five pregnancies complicated by preeclampsia, three of them have preexisting HTN, thirty patients (50%) underwent vaginal delivery, twenty patients (33%) underwent cesarean section due to different obstetric indications (previous cesareans and preeclampsia). Thirteen neonates (26%) were born with low birth weight, and two neonates (3%) required neonatal intensive care unit admission; no neonatal cases of lupus or congenital cardiac problems were reported. Postnatal SLE flare was reported among 16 patients (53%); preexisting HTN was strongly associated with preeclampsia, preterm labor, and postnatal SLE flares (P-values were 0.001, 0.003, and 0.004, respectively), whereas secondary Antiphospholipid antibody syndrome (APL) was associated with preeclampsia and abortion (P = 0.005 and 0.002). Conclusion: Preexisting HTN and secondary APL are associated with an increased risk of pregnancy complications. Characteristics and outcomes in our series are comparable to previously published international cohorts.
Keywords: Fetal outcomes; intrauterine fetal deaths; Libya; maternal; pregnancy; spontaneous abortion; systemic lupus erythematosus